Digital twin tackles design challenges. Issue 4 (April 2017) - Ferguson, Stephen; Bennett, Edward; Ivashchenko, Artem
Abstract : The US-based Mechanical Solutions Inc. (MSI) specializes in analysis and testing of rotating and reciprocating turbomachines. This article looks at how it used a simulation package from Siemens PLM Software to tackle design challenges in water pumps.